Lonto Leok Model in Contextual Catechesis of Manggaraian Local Church - Habur, Agustinus Manfred (STKIP Santu Paulus Ruteng, 2016)
Catechesis, as educational process of faith, is always contextual because faith is essentially dealt with real life context.Therefore, Catechesis of Manggaraian local church must be contextual. It touches the flavors of genuinelife of people in one place. An appropriate approach for this contextual catehesis is lonto leok model inwhich people discuss problems in the light of Christian faith.Lonto leok catechesis is actually conductedinKBG.Theemphasis is still put on practical hermeneutics as a current model which can not truly help thepeople to be personally in contact with Christ, the Divine Word of life. The future lonto leokcatechesisshould promote Easter hermeneutics that sees life as a mystery of mission calling the people to bring theKingdom of God in the world. In this way, lonto leokcatechesis can guide the Manggaraian followers to besolid, independent, and solider in faith.Keywords: â€œlonto leokâ€, contextual catechesis, Manggaraian local church